Knowledge for development: The IDB's impact in the region - Leopoldo Avellán; Claudia Calderón; Giulia Lotti; Z'leste Wanner (Inter-American Development Bank (IDB), 2021)
By analyzing a novel dataset on publications by the Inter - American Development Bank (IDB), we shed light on the extent to which the knowledge production of a multilateral development bank can reach its beneficiaries. We find that IDB publications are downl oaded mostly in the American continent, with Peru , Colombia, the United States and Mexico leading the ranking in 2020 . Moreover, during the C OVID - 19 pandemic downloads of IDB publications increased, both in the world and in Latin America and the Caribbean . S ome characteristics of publications are significantly associated with higher numbers of downloads , such as the language of publications: documents in at least two languages or in Spanish only are downloaded more often than documents in English only, sugg esting that it is important to disseminate research in the language of the targeted audience. As for the online discussion on the IDB, we find that mentions of the IDB touch different sectors important for development (especially modernization of the state , health, labor markets and financial markets), and that they increase when a document is published.
Keywords: O19; 330; knowledge; multilateral development banks; research impact; social media; policymakers